Readability and conventionality in expository texts in Brazilian Portuguese (Revista de Estudos da Linguagem, 2024)
The aim of this research is to collate data from intelligibility and conventionality in health-related expository texts in Portuguese to investigate their appropriateness to Brazilians. To this end, we rely on Corpus Linguistics for the compilation and processing of a parallel corpus, comprising texts originally written in English and their translations into Portuguese, and a comparable corpus, composed of texts translated into Portuguese and texts originally written in that language. Our methodology combines quantitative analysis – to assess readability, keyness, and collocation – and qualitative analysis – to investigate words in context. Regarding readability, the tools pointed out that texts written in Portuguese are ‘difficult’ for the average Brazilian reader, with a level of education lower than High School. The translated texts were considered ‘fairly difficult’, according to this same evaluation criterion, which classified the originals in English as ‘fairly easy’, considering its target audience, that is, the average American reader. The qualitative analysis pointed out that the translated texts may compromise conventionality, revealing a preference for prima facie equivalents, not always consistent with the patterns observed in original Brazilian Portuguese counterparts. Although the accessibility evaluation tool indicates that both the texts originally written in Portuguese and those translated into Portuguese do not prove to be entirely suitable for the Brazilian target reader of medical expository texts, we believe that, by breaking conventionality, the translated texts may hinder even more the average reader’s comprehension of results of scientific research.